The Contribution of Big Five Personality Traits as Determinants Marital Adjustment in Wives Married 1-5 Years - Gultom, Gratia Eunike Dameria; Yuliastuti Endang Kusumiati, Ratriana (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Differences in perspectives and habits trigger conflicts early in marriage. This situation necessitates marital adjustment, and personality serves as a determining factor in the success of such adjustment. Therefore, the objective of this study is to examine the correlation between the Big Five personality traits and marital adjustment among wives who have been married for 1–5 years in Salatiga. This study employs a correlational approach using accidental sampling. The results indicate that the traits of extraversion, agreeableness, conscientiousness, and openness to experience have a positive correlation with marital adjustment, whereas the trait of neuroticism has a negative correlation with marital adjustment. This study demonstrates that personality traits exert a significant influence on an individual’s attitude during the process of marital adjustment. Perbedaan pandangan dan kebiasaan memicu benturan di awal pernikahan. Kondisi ini menuntut adanya penyesuaian perkawinan dan kepribadian menjadi faktor penentu keberhasilan penyesuaian perkawinan. Oleh karena itu, tujuan dari penelitian ini adalah untuk melihat korelasi big five personality traits terhadap penyesuaian perkawinan pada istri dengan usia pernikahan 1-5 tahun di Salatiga. Penelitian ini menggunakan pendekatan korelasional dengan teknik accidental sampling. Hasil penelitian menunjukkan bahwa trait extraversion, agreeableness, conscientiousness, dan openness to experience memiliki korelasi yang positif terhadap penyesuaian perkawinan, sementara itu, trait neuroticism memiliki korelasi negatif terhadap penyesuaian perkawinan. Penelitian ini memberikan pemahaman bahwa trait kepribadian memegang kendali penuh atas sikap seseorang saat melakukan penyesuaian perkawinan.